The understanding of inclusion in education of pre-service primary school teachers who graduated from a public university in Zimbabwe: Conceptualising inclusion in education - Chipika, Charles Govero; Mapfunde, Davie (Educenter : Jurnal Ilmiah Pendidikan, 2025)
Since the universalisation of inclusive education in 1994 at the United Nations Salamanca Conference in Spain, teachers globally have been grappling with how to implement it. Inclusive education calls for adoption of inclusive pedagogical approaches that are learner-centred. In order to do justice to diverse learners in today’s heterogeneous classroom populations, a solid and in-depth understanding of the philosophy of inclusion is a pre-requisite for all classroom practitioners. This qualitative study therefore aims to examine the understanding of inclusion in education of pre-service primary school teachers who graduated from a public university in Zimbabwe as the context for proposing strategies to enhance their professional preparation. Sixteen graduate pre-service primary school teachers who were purposively sampled from Masvingo province’s selected university that proffers pre-service teacher education. A triangulation of data gathering instruments of face-to-face individual interviews, document analysis and non-participant observation complemented by a follow-up discussion was adopted. Data gathered was thematically analysed and established several findings. The chief finding was that, university graduate pre-service primary school teachers had differing and inadequate understandings of the philosophy of inclusion in education that culminated into haphazard implementation of inclusive education as they had various practices.